War Workers Hostels, 1941 (pg. 2) (United Kingdom, 1941)
1941 1939-1945 "War Workers Hostels, 1941 (pg. 2)" [HFR0053b], 1941 The dispersal of factories and the building of Royal Ordnance Factories in isolated areas required residential hostels to be built for war workers. The first was opened in January 1941 and a National Service Hostels Corporation [with Margaret Bondfield as one of the directors] was established. By the end of the war, the Corporation was managing 155 hostels with accommodation for 36,000 industrial workers, 17,500 miners and over 18,500 building workers. Separate hostels were built for young miners and agricultural workers. Workers slept in single bunk cubicles and there was a sick bay, dining room and welfare facilities. Charges ranged between 25-30 shillings a week and included 2 full meals plus a snack daily.